Fate of Drilling Fluids during the South McMurdo Sound Project (SMS) of the Antarctic Geological Drilling Program (ANDRILL) - Lenczewski, Melissa (IEDA: US Antarctic Program Data Center, 2014)
Abstract: The PI proposes to utilize computer models used by hydrogeologists to establish the fate and transport of contamination and determine the extent of drilling fluid contamination in the ANDRILL SMS core. For these models, previously collected logs of lithology, porosity, fracture density, fracture type, fracture orientation, drilling fluid loss, drilling fluid characteristics and temperature will be used as input parameters. In addition, biodegradation and sorption constants for the drilling fluid will be determined and incorporated into the models. Samples of drilling fluids used during coring as well as the return fluids were collected at the drill site using standard microbiological sampling techniques. Fluids will be tested at in situ temperatures under aerobic and anaerobic conditions to determine biodegradation constants. Sorption will be determined between the drilling fluids and core samples using standard isotherm methods. Geochemical and microbial fingerprints of the fluids and the changes during biodegradation will determine the potential impact of the drilling fluids on the isolated microbial communities and the geochemistry within various subsurface lithologic units beneath the southern McMurdo Sound in Antarctica. The results of this study could potentially provide guidelines on developing less detrimental methods for future exploration, if deemed necessary through this research. This proposed project will train a graduate student. The methods developed for analyses of samples in this project will serve as a guide for future studies of similar interest and will improve the understanding of ecological impacts of geologic drilling in Antarctica. The results of this study will be used as a reference for comparison with future studies examining newly developed, and improved, sample collection methods in future exploratory drilling projects in pristine environments. The PI is new to Antarctic research.